POTENSI METODE OPTIK UNTUK PENDUGAAN KANDUNGAN ANTOSIANIN PADA BUAH BLACK MULBERRY DAN STROBERI - Jajang Juansah (Jurnal Biofisika, 2013)
Estimation of pigment in plant tissues can be studied from optical properties. Reflectance spectra of optics signal on black mulberry and strawberry fruit have been studied for nondestructive estimation of anthocyanin pigment content. In addition, the absorbance spectra were also studied in fruit extracts with different solvent types, ie: a combined solution of tartaric acid and ethanol - chloric acid. The results showed that there is energy absorption for chlorophyll a in the blue area, i.e.: 465 nm- black mulberry and 478 nm-strawberry. While the energy absorption for chlorophyll b occurs in the red region with a wavelength of 650 nm (black mulberry) and 655 nm (strawberry). Maximum peak absorbance of anthocyanin pigments of black mulberry fruit with tartaric acid solvent had occurred at 515 nm. While for the solvent ethanol -hydrochloric acid has occurred at a wavelength of 519 nm.